2011
DOI: 10.1155/2011/926361
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroid Binding Sites on the GABAAReceptor Complex as Novel Targets for Therapeutics to Reduce Alcohol Abuse and Dependence

Abstract: Despite the prevalence of alcohol abuse and dependence in the US and Europe, there are only five approved pharmacotherapies for alcohol dependence. Moreover, these pharmacotherapeutic options have limited clinical utility. The purpose of this paper is to present pertinent literature suggesting that both alcohol and the neurosteroids interact at the GABAA receptor complex and that the neurosteroid sites on this receptor complex could serve as new targets for the development of novel therapeutics for alcohol abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…Operant self-administration as employed in the mice studies (Cruz et al, 2008; García-Gutiérrez et al, 2016) measures motivation (June & Gilpin, 2010), while our two-bottle choice paradigm better measures ethanol preference (Rhodes et al, 2005). Moreover, a previous study (Hulin, Amato, Porter, Filipeanu, & Winsauer, 2011) reported that the two paradigms, (i.e., ethanol self-administration in the home cage versus operant chamber), produced very different ethanol intake patterns. Nevertheless, our results corroborate some existing results suggesting that reduced maternal care may not affect adolescent ethanol consumption and preference in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Operant self-administration as employed in the mice studies (Cruz et al, 2008; García-Gutiérrez et al, 2016) measures motivation (June & Gilpin, 2010), while our two-bottle choice paradigm better measures ethanol preference (Rhodes et al, 2005). Moreover, a previous study (Hulin, Amato, Porter, Filipeanu, & Winsauer, 2011) reported that the two paradigms, (i.e., ethanol self-administration in the home cage versus operant chamber), produced very different ethanol intake patterns. Nevertheless, our results corroborate some existing results suggesting that reduced maternal care may not affect adolescent ethanol consumption and preference in rats.…”
Section: Discussionmentioning
confidence: 99%
“…For example, metyrapone may also increase dehydroepiandrosterone (DHEA), an androgenic precursor and one of the most abundant steroid metabolites, possessing both genomic and nongenomic actions [56,73,95,96]. DHEA has also been demonstrated to decrease cocaine-and alcoholrelated behaviors and may contribute to the efficacy of metyrapone [97][98][99][100].…”
Section: Discussionmentioning
confidence: 99%
“…As high ethanol intake promotes neurosteroid synthesis, they are capable of activating GABA-A receptors even at nanomolar concentrations . For a competitive GABA-A receptor antagonist (SR 95531), when administered directly into the central nucleus of the amygdala, a decrease in alcohol intake was observed . Thus, neurosteroids could be a potential target in alcoholic patients due to their vital role in regulating the activity of GABA-A receptors.…”
Section: Recent Approaches Toward the Treatment Of Alcohol Addictionmentioning
confidence: 99%